(untitled) (International Journal of Food and Nutritional Sciences, 2022)
As the healthcare industry continues to evolve, the integration of cloud computing technologies has emerged as a transformative force, particularly in the realm of health care learning systems. This research paper explores the recent developments and applications of cloud computing in healthcare education, focusing on the impact on learning systems, training, and knowledge dissemination. The paper reviews current trends, challenges, and opportunities in leveraging cloud-based solutions for medical education and professional development. By examining case studies and real-world implementations, the paper aims to provide insights into the potential benefits of cloud computing in enhancing the efficiency, accessibility, and effectiveness of healthcare learning systems.